Substratal idiothetic navigation of rats is impaired by removal or devaluation of extramaze and intramaze cues - Stuchlik, A; Fenton, A A; Bures, J (Proceedings of the National Academy of Sciences of the United States of America, 2001)
The spatial orientation of vertebrates is implemented by two complementary mechanisms: allothesis, processing the information about spatial relationships between the animal and perceptible landmarks, and idiothesis, processing the substratal and inertial information produced by the animal's active or passive movement through the environment. Both systems allow the animal to compute its position with respect to perceptible landmarks and to the already traversed portion of the path. In the present study, we examined the properties of substratal idiothesis deprived of relevant exteroceptive information. Rats searching for food pellets in an arena formed by a movable inner disk and a peripheral immobile belt were trained in darkness to avoid a 60 degrees sector; rats that entered this sector received a mild foot shock. The punished sector was defined in the substratal idiothetic frame, and the rats had to determine the location of the shock sector with the use of substratal idiothesis only, because all putative intramaze cues were made irrelevant by angular displacements of the disk relative to the belt. Striking impairment of place avoidance by this "shuffling procedure" indicates that effective substratal idiothesis must be updated by exteroceptive intramaze cues.
Keywords: plnění a analýza úkolů; Rats, Long-Evans; krysa rodu Rattus; Animals; Avoidance Learning; Spatial Behavior; reverzní učení; mužské pohlaví; podněty; zvířata; potkani Long-Evans; Male; učení vyhýbat se; Cues; Rats; prostorové chování; Reversal Learning; Task Performance and Analysis